Synthesis, Characterization and Permeance Evaluation of Nanofiller-Enhanced Polyvinyl Alcohol/Potassium Formate-Based Membranes - Abdullah, Shekh; Zubir, Mohd Nashrul Bin Mohd; Muhamad, Mohd Ridha Bin; Newaz, Kazi Md Salim; Öztop, Hakan Fehmi; Yu, Lim Jing; Shaikh, Kaleemullah (Springer, 2024)
Achievement of thermal comfort in air conditioning is a vital issue in the verge of global warming, where it is essential to provide a system that is less harmful to the environment, energy-efficient and economical. In this regard, dehumidification plays an important role in achieving thermal comfort of air conditioning system. Most of the dehumidification systems as of now require high energy and induce negative environmental impacts. Recently a vacuum membrane-based dehumidification has been considered for the alternative air-conditioning system. Development of efficient membranes for the dehumidification operation is indispensable for moisture removal. Typically, the membrane is constructed out of a fine and porous twilled Dutch weave stainless steel wire mesh serving as the support structure laminated with a film of active materials that serve to attract and isolate the moisture from the working air. In this work a combination of nanomaterial and hygroscopic polymer was adopted to improve the film functionality on the wire mesh. In particular, titanium dioxide (TiO2) is coated as intermediate layer on the wire mesh. Further, Polyvinyl alcohol (PVA) and various concentration of potassium formate (KCOOH) were used as the active additive material aiming to increase sensitivity of the membrane towards water vapor. The water vapor and air permeability tests were conducted to investigate the water vapor permeation and air selectivity of the membrane under various air conditions. Morphological and permeance analogy of the produced membrane showed that adding KCOOH enhanced hydrophilicity, which also increased water vapor permeability by 720%.
Keywords: Vapor compression system; Desiccant; Membrane; Permeability; Polyvinyl alcohol; Potassium formate